2022
DOI: 10.3390/biology11081204
|View full text |Cite
|
Sign up to set email alerts
|

The “Infernaccio” Gorges: Microbial Diversity of Black Deposits and Isolation of Manganese-Solubilizing Bacteria

Abstract: The present study explored the microbial diversity of black deposits found in the “Infernaccio” gorge. X-ray Powdered Diffraction (XRPD) was used to investigate the crystallinity of the samples and to identify the minerals. Scanning electron microscope and energy-dispersive X-ray spectroscopy (SEM-EDS) were used to detect the bacterial imprints, analyze microbe–mineral interactions, and highlight the chemical element distribution in the black deposits. 16S rRNA gene metabarcoding allowed the study of Archaea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The results of the morphological characterization of the calcifying strains collected during this study showed the prevalence (67%) of Gram-positive bacteria; only strains B4, B6 and B15 were Gram-negative. This finding is in line with the results of previous studies [41] , [42] . Among all studied bacteria, 7 strains (A7, A11, A14, LMG 11351, B4, B6 and B15), all GN bacteria, were selected for further analysis based on their ability to precipitate CaCO 3 in vitro .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The results of the morphological characterization of the calcifying strains collected during this study showed the prevalence (67%) of Gram-positive bacteria; only strains B4, B6 and B15 were Gram-negative. This finding is in line with the results of previous studies [41] , [42] . Among all studied bacteria, 7 strains (A7, A11, A14, LMG 11351, B4, B6 and B15), all GN bacteria, were selected for further analysis based on their ability to precipitate CaCO 3 in vitro .…”
Section: Resultssupporting
confidence: 94%
“…Inoculated B-4 plates were incubated at 27 °C for 7 days. All colony types were then described based on pigmentation, form, elevation, margin, opacity and surface area [42] . Colonies were classified according to morphology and chromatogenesis and characterized by cell shape and Gram type determination using the Gram 2 Kit (bioMérieux, Marcy-l'Etoile, France).…”
Section: Methodsmentioning
confidence: 99%
“…Microbial contribution is usually described by the mineralization/lithification of microbial cells and their aggregation structures, such as biofilms 12 , which can occur internally and externally. Many authors have described the presence of these biosignatures for several speleothems 15 18 . Our previous investigations described already the presence of these imprints within “Grotta Grande dei Cervi” black deposits 12 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Microbial contribution is usually described by the mineralization/ lithification of microbial cells and their aggregation structures, such as biofilms 12 , which can occur internally and externally. Many authors have described the presence of these biosignatures for several speleothems [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation